2007
DOI: 10.1002/qua.21510
|View full text |Cite
|
Sign up to set email alerts
|

Improving the TDDFT calculation of low‐lying excited states for polycyclic aromatic hydrocarbons using the Tamm–Dancoff approximation

Abstract: L a states for a series of linear acenes showed that a TDDFT scheme incorporating the Tamm-Dancoff approximation (TDDFT/ TDA) could decrease the estimation errors by a factor of about 50%, but keep the levels of 1 L b states almost unchanged. Thus, the TDDFT/TDA scheme gives an overall description for the low-lying excited states of linear acenes significantly better than the full TDDFT does. Furthermore, 16 nonlinear polycyclic aromatic hydrocarbons (PAHs) with various structures were examined to confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 34 publications
6
82
0
Order By: Relevance
“…As TDDFT has difficulties to locate the region of conical intersection, for the points close to it we have used the Tamm-Dancoff approximation, TDDFT-DA. 49 The results shown in Figure 6 confirm the conclusion of the importance of the branching coordinate and the role of the antibonding interaction within the LUMO for ringopening. The conical intersection is located at larger torsion angles and at a short distance between the ring-closing carbon atoms.…”
Section: Resultssupporting
confidence: 70%
“…As TDDFT has difficulties to locate the region of conical intersection, for the points close to it we have used the Tamm-Dancoff approximation, TDDFT-DA. 49 The results shown in Figure 6 confirm the conclusion of the importance of the branching coordinate and the role of the antibonding interaction within the LUMO for ringopening. The conical intersection is located at larger torsion angles and at a short distance between the ring-closing carbon atoms.…”
Section: Resultssupporting
confidence: 70%
“…The excited-state transition energies and oscillator strengths were obtained by means of both full time-dependent DFT (TDDFT) calculations and TDDFT calculations based on the Tamm-Dancoff approximation (TDA-TDDFT). [24][25][26] In addition, the lowest CT energy of the P/C 60 complex was obtained by means of a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 constrained DFT (CDFT) approach. 27,28 The impact of HF exchange was also investigated by using the αPBE functional, based on the original PBE functional, 29,30 following the simple hybrid scheme proposed by Adamo and Barone: 31…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Such a scenario would be consistent with 1 H-NMR data on the rotary cycle of a second-generation motor with a dibenzocyclohepten-5-ylidene stator, 26 but is not a common feature for second-generation motors. 26 Specifically, the first piece of evidence that the stator-rotator folding changes Performing excited-state geometry optimizations using time-dependent DFT (TD-DFT) [77][78][79][80][81][82][83][84][85] within the Tamm-Dancoff approximation (TDA) [86][87][88][89] and also using the ab initio approximate coupled-cluster singles and doubles (CC2) method 90 as implemented in the Turbomole 6.3 suite of programs, 91,92 key results from these calculations are presented in Table 1. From Table 1, it is found that the stator-rotator folding relative to the olefinic Finally, as to verifying that the photochemical steps sustain rotary motion, this can indeed be inferred from the observation in Table 1 that the changes in the α dihedral angle during the FC relaxation have the same sign (…”
Section: Syn-and Anti-folded Isomers Of Motormentioning
confidence: 99%